Soil physico – chemical properties of different topography under oil palm cultivation / Nur Atikah Samsudin - Samsudin, Nur Atikah (Faculty of Plantation and Agrotechnology, 2018)
Topography is one of the potential factors that has influence on soil properties and effect the production of FFB yield in oil palm cultivation. The study was conducted to evaluate the effect of different topography (flat and undulating) with two different depth (0-15 cm) and (15-30 cm) at RISDA Palong Plantation Estate on soil texture and selected soil chemical properties. A 2 x 2 factorial ANOVA was used as the experimental design and all the data for parameters studied were tested using SPSS. Results on the effect of soil topography with two different depths on selected soil properties showed that the combination factors of topography and depth affected the soil pH, cation exchange capacity and also exchangeable potassium. Soil organic matter, available phosphorus, exchangeable bases (Ca, and Mg) as well as exchangeable acidity (Al) were not affected by the combination factors of soil topography and soil depth.